2010
DOI: 10.1002/acp.1697
|View full text |Cite
|
Sign up to set email alerts
|

Current directions at the juncture of clinical and cognitive science: A commentary on the special issue

Abstract: The 12 experimental papers presented in this special issue brilliantly illustrate the creative and exciting ways in which the exchange of theoretical concepts and experimental methodologies, between cognitive and clinical science, is serving both to deepen our understanding of psychopathology, and to identify new ways of potentially remediating such dysfunction. These papers are not only individually excellent, but collectively they communicate some of the major themes that are presently driving new developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…These results contrast sharply with the self-report measure, in which participants reported intoxication for all alcohol concentration conditions. Consistent with our findings, previous studies using both self-report and IAT indices have found that these indices do not necessarily behave in the same way [ 32 , 33 ], suggesting that each of these measures reveals different aspects of cognitive processing (see [ 34 ] for a review). The IAT, in particular, focuses on internal proximity between concepts and attributes in the absence of intentional responses.…”
Section: Discussionsupporting
confidence: 90%
“…These results contrast sharply with the self-report measure, in which participants reported intoxication for all alcohol concentration conditions. Consistent with our findings, previous studies using both self-report and IAT indices have found that these indices do not necessarily behave in the same way [ 32 , 33 ], suggesting that each of these measures reveals different aspects of cognitive processing (see [ 34 ] for a review). The IAT, in particular, focuses on internal proximity between concepts and attributes in the absence of intentional responses.…”
Section: Discussionsupporting
confidence: 90%
“…The Stroop cognitive task, in turn, is arguably the most widely used selective attention task in cognitive science (Eidels et al, 2010 ). Its ascendant popularity extends to clinical cognitive science (Macleod, 2010 ), including that directed to cognition in Sz (e.g., Minzenberg et al, 2009 ). In a typical Stroop task as used in clinical cognitive science, performance requires the naming of a color in which a word is written.…”
Section: Introductionmentioning
confidence: 99%
“…These results offer support for the cognitive model of OCD, which emphasises the importance of appraisals of intrusive thoughts, and provide initial evidence that modifying interpretation biases in a high OC population may have downstream effects on emotional and physiological responses to OC stressors. The inclusion of a behavioural measure in this study was important to provide a robust test of the effects of CBM on emotional consequences that is not confounded by the potential for self-report bias [ 29 ]. However, OCD experts have identified six core appraisals implicated in OCD symptom maintenance: 1) Tolerance for Uncertainty (e.g., ' It is essential for me to consider all possible outcomes of a situation’ ), 2) Threat Estimation (e.g., ' I often think things around me are unsafe’ ), 3) Control of Thoughts (e.g., ' I should be able to rid my mind of unwanted thoughts’ ), 4) Importance of Thoughts (e.g., ' Having nasty thoughts means I am a terrible person’ ), 5) Responsibility (e.g., ' If my actions could have even a small effect on a potential misfortune, I am responsible for the outcome’ ) and 6) Perfectionism (e.g., ' If I don’t do a job perfectly, people won’t respect me’ ).…”
Section: Introductionmentioning
confidence: 99%